REVOLUSI DIGITAL DALAM RUANG SUCI: DAMPAK TEKNOLOGI TERHADAP PRAKTIK DAN PENGALAMAN KEAGAMAAN - Lucia Martins; Selviana Veonika Moruk; Zelio da Conceição freitas (Al Naqdu, 2025)
This research examines the impact of the digital revolution on religious practices and experiences, focusing on the transformation of individual interactions with beliefs through digital technology. A qualitative approach was used in a case study of a number of religious communities in Indonesia that actively use social media. The data was obtained through in-depth interviews with religious leaders and congregation members, as well as content analysis of their uploads and activities on social media. The results of the study show that digital technology expands the dissemination of religious information, forms virtual communities, and changes the pattern of worship and ritual implementation. However, the study also found challenges, such as the spread of false information, polarization, and commercialization of religious teachings. Therefore, strong digital literacy and the development of inclusive and responsible digital platforms are indispensable in supporting religious diversity in the digital era